Diagnostic efficiency of exome-based sequencing in pediatric patients with epilepsy - Zou, Huafang; Zhang, Qian; Liao, Jianxiang; Zou, Dongfang; Hu, Zhanqi; Li, Bing; Chen, Li; Wen, Jialun; Zhao, Xia; Zhang, Victor Wei; Cao, Dezhi (Frontiers in Genetics, 2025)
ObjectiveEpilepsy, a prevalent neurological disorder, has multifaceted etiologies. Next-generation sequencing (NGS) has emerged as a robust diagnostic tool for this condition. This study aims to evaluate the detection efficiencies of different exome-based sequencing techniques.MethodsExome-based epilepsy panel tests, clinical exome sequencing (CES), and whole exome sequencing (WES) were conducted on 259 pediatric patients diagnosed with epilepsy. Single-nucleotide variants (SNVs) and copy number variants (CNVs) were interpreted based on each patient’s phenotypic presentation. Additionally, data concerning clinical symptoms, neuroimaging findings, treatment responses, and prognostic outcomes were collected and analyzed.ResultsThe overall diagnostic yield was 32.8% (85/259), with a diagnostic yield of 40.0% for exome-based epilepsy panels, 30.1% for CES, and 27.8% for WES. We identified 82 cases with pathogenic or likely pathogenic SNVs and 4 cases with pathogenic CNVs, of which one case with both SNV and CNV. The most frequently detected gene was PRRT2, present in 10.0% (9/82) of cases. Epileptic syndromes were diagnosed in 66 patients, predominantly West Syndrome, Dravet Syndrome and Genetic Epilepsy with Febrile Seizures plus.ConclusionNGS is an effective method for uncovering the genetic foundations of pediatric epilepsy, with diagnostic yields varying based on the sequencing approach used. The growing preference for WES underscores its utility in complex cases, pointing to a trend towards more tailored diagnostic strategies.